Hidradenitis Suppurativa-An intractable Dermo- Surgical Disease - Muhammad Ateeq , Shazia Jehan (Journal of Rawalpindi Medical College, 2012)
Background: To study the surgical management outcome of Hidradenitis suppurativa Methods: In this descriptive study, patients presenting with Hidradenitis suppurativa were analyzed with reference to presentation and surgical management outcome. Results: Out of 31 patients 3 (09.67%) patients were male and 28 (90.32%) were female. Mean duration of onset of disease and presentation was 15 months. Axilla was the commonest site involved(74.19%) followed by inframammary fold (19.35%). Nine (29.03%) patients presented in the emergency in the form of single or multiple abscess requiring incision & drainage. Excision and primary skin grafting was the most frequent surgical procedure performed in 54.83% with acceptable outcome. Conclusion: Hidradenitis suppurativa needs individualized patient based management strategy with close collaboration of surgeon and dermatologist